(untitled) (Revista Contexto & Saúde, 2025)
Kombucha is a fermented beverage produced by a symbiotic culture of microbiologically active bacteria and yeast (SCOBY) with properties that are reportedly beneficial to health. A descriptive study was conducted with kombuchas produced on a small scale in Porto Alegre/RS. Samples were collected to isolate microorganisms present in the kombucha, as well as in the ingredients used (SCOBY and green tea). The beverages were analyzed in their original and flavored versions, with and without homogenization, in triplicate, totaling 12 samples. It was found that kombucha exhibited a high yeast count, with a significant difference in the beverage depending on homogenization, both in the homogenized original version (7.39±6.46 log CFU/mL vs. non-homogenized 6.46±5.39 log CFU/mL, p<0.0065) and in the homogenized flavored version (7.54±6.81 log CFU/mL vs. non-homogenized 7.20±6.04 log CFU/mL, p<0.049). The SCOBY presented a total yeast count of 6.78±6.68 log CFU/mL, and no microbial growth was observed in the green tea. In conclusion, the analyzed kombucha exhibited a high yeast content in both the original and flavored versions, with a higher concentration of these microorganisms in the homogenized form, suggesting the importance of mild homogenization of the beverage before consumption.